Transformational Leadership and Digital Transformation: Bridging Strategy and Culture in the Era of Industry 5.0 - Shankar Subramanian Iyer; Brinitha Raji; Sangeeta Malhotra (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2026)
Background: Digital transformation initiatives frequently fail despite substantial investments, with success rates remaining below 30% across industries. Objectives: This study investigated the critical determinants of successful digital transformation in Industry 5.0 contexts by integrating five theoretical frameworks to examine four key constructs: Transformational Leadership Attributes, Strategic Alignment and Vision, Organizational Culture for Innovation, and Human-Centric Design and Employee Readiness. Methods: Employing a qualitative, interpretivist multiple-case design, the study drew upon 18 semi-structured interviews conducted across three case entities, each featuring C-level executives and senior managers as informants. Analytical procedures followed Braun and Clarke’s six-stage framework for thematic analysis, applied to the transcribed corpus. Findings: Five overarching themes emerged: (1) Visionary Leadership as the Catalyst for Transformation, (2) Strategic Alignment and Agility, (3) Culture as the Foundation for Innovation, (4) Human-Centric Design and Employee Empowerment, and (5) Technology as an Enabler. Conclusion: This study provided the first qualitative, cross-national empirical evidence integrating all four determinants simultaneously in Industry 5.0 contexts, demonstrating that successful digital transformation requires synchronized orchestration of leadership vision, strategic agility, cultural readiness, and human-centric technology integration. The findings offer actionable insights for organizations navigating the industry 4.0 to 5.0 transition.